A Longitudinal Analysis of Adolescent Smoking: Using Smoking Status to Differentiate the Influence of Body Weight Measures. (21st March 2013) - Hong, Traci; Johnson, Carolyn
ABSTRACT: BACKGROUND: Previous research has reported mixed results on the association between body weight measures (ie, perception of weight and weight loss goal) and cigarette smoking prevalence—and how these associations vary by sex and race. This longitudinal study assessed the relationship between these 2 body weight measures and smoking prevalence by smoking status (ie, nonsmoker, former smoker, smoker). METHODS: Panel data of adolescents (N = 1592) from Louisiana schools completed survey interviews in the 9th grade and again in the 12th grade. Three separate ordinary least squares (OLS) regression analyses were conducted based on respondents' smoking status in the 9th grade: nonsmoker, former smoker, and smoker. The dependent variable, smoking prevalence was assessed in the 12th grade. RESULTS: Among nonsmokers, weight loss goal was associated with smoking in the 12th grade. Among former smokers, the association between weight loss goal and smoking varied by sex. Girls who reported the goal to lose weight smoked more than their male counterparts. In contrast, among those who did not have the goal of losing weight, boys smoked more than girls. Among adolescents who were already smokers in the 9th grade, weight loss goal was not significantly associated with smoking prevalence. CONCLUSION: Differences in the association between weight‐related variables and smoking prevalence may be attributed, in part, to smoking status. School‐based smoking interventions should target nonsmokers and female former smokers who desire weight loss.